THE EFFECT OF FINGER PAINTING ON FINE MOTOR DEVELOPMENT IN CHILDREN IN ACEH: A CASE STUDY - Mohd. Rizal Fahmi Adha; Siti Nurafifah Qarimah (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Fine motor skills involve the use of small muscles, such as those in the fingers and wrist, working in coordination with the eyes and hands to achieve specific skills with precision. Delays in fine motor skills, if not addressed, can lead to various consequences such as a lack of interest in learning and creativity. One way to improve children's fine motor skills is through finger painting activities. Finger painting engages the small muscles in the wrist, arms, and fingers, while coordinating with the eyes and brain, thus helping to enhance fine motor development. This study aims to assess the implementation of finger painting activities in improving fine motor skills in preschool children, involving two children in Aceh. This descriptive study uses a case study approach, with data collected through interviews and observations before and after the finger painting activity. The study was conducted over 7 days at a Kindergarten in Aceh. The results showed that finger painting activities were effective in improving fine motor skills. For Subject I, an improvement in fine motor skills was observed after the finger painting activity was implemented. The same result was found for Subject II, with an increase in fine motor skills before and after the activity. It is expected that the implementation of finger painting activities can be applied as a method to enhance fine motor skills in preschool children.